2012
DOI: 10.1007/s12088-012-0264-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial Activity of Bauhinia purpurea Leaves Under In Vitro Conditions

Abstract: This study was undertaken with an objective of testing the antibacterial and antifungal activities of Bauhinia purpurea leaves and identifying the bioactive compounds. The antimicrobial activity of leaf extract was determined in aqueous and organic extracts and the minimum inhibitory concentration (MIC) against six species of pathogenic and non-pathogenic microorganisms: Bacillus subtilis, Staphylococcus aureus, Salmonella typhi, Escherichia coli, Pseudomonas aeruginosa and Candida albicans using the disk diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 13 publications
0
12
0
2
Order By: Relevance
“…In this way it differs from other antibiotics produced by a tunicate, the Styela clava which produces styelin and clavanin, that are active against both Gram-positive and Gram-negative bacteria [14]. The synergism activities between substances extracted from natural organisms may contribute to antimicrobial ability but the mechanisms of action are complicated to predict [21].…”
Section: Characterization Of Sbe Via Gcms and Identification Of Bio-amentioning
confidence: 99%
“…In this way it differs from other antibiotics produced by a tunicate, the Styela clava which produces styelin and clavanin, that are active against both Gram-positive and Gram-negative bacteria [14]. The synergism activities between substances extracted from natural organisms may contribute to antimicrobial ability but the mechanisms of action are complicated to predict [21].…”
Section: Characterization Of Sbe Via Gcms and Identification Of Bio-amentioning
confidence: 99%
“…Bauhinia purpurea is also found in Myanmar, Sri Lanka and Southern China. 34 Bauhinia purpurea leaves, owers, ower buds, and young pods are edible 35 and have medicinal value, exhibiting antioxidant, 36 anti-cancer, 37 anti-microbial, 38 and nephroprotective 39 activities. Bauhinia purpurea can withstand aqueous pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the plant exhibited antimicrobial [8], antinociceptive, anti-inflammatory, and antipyretic [3, 9], antimycobacterial, antimalarial, antifungal, cytotoxic, and anti-inflammatory [10], anti-nephrotoxicity [11], and wound healing [12] activities. In vitro study has demonstrated that B. purpurea possesses antiproliferative [13], antioxidant [13, 14], and antimicrobial activities [14, 15], and also has potential as hepatocellular carcinoma inhibitor [16]. Interestingly, other studies have proved that B. purpurea leaf possesses antiulcer activity [17, 18].…”
Section: Introductionmentioning
confidence: 99%